Evaluating behavioural changes for climate adaptation planning. Issue 7 (7th June 2023) - Walawalkar, Tanvi P.; Hermans, Leon M.; Evers, Jaap
Abstract : Most climate adaptation plans expect stakeholders to change their behavior as part of building resilience. Given its long-term and complex nature, monitoring and evaluation is a key requisite for climate adaptation planning. So far, behavioral aspects have received only limited attention in the evaluation approaches for climate adaptation planning. This article proposes a theory-based evaluation approach based on the theory of planned behavior, for the evaluation of climate adaptation. A local climate adaptation programme for watershed development in rural India provides an illustrative case for this approach. For this case, the approach helped to uncover important factors that influence behavioral intentions, which were different for different groups in the farming community. Additionally, it helped to put behavioral change in a longer-term perspective. The illustrative case also suggests certain improvements for evaluations based on the theory of planned behavior.